The Marginalization of People of Colour through White-guilt in Abdulrazak Gurnah’s Admiring Silence - Shaaban Sulaiman Sadeeq; Diyar Jamal Mohammed (QALAAI ZANIST JOURNAL, 2022)
This article explores the notion of white guilt and how it is weaponised, consciously or subconsciously, in the marginalisation of people of colour (POC), especially the Africans in the diaspora. It aims to show how white guilt changes its meaning from positive to negative when not controlled. This medium attempt to explain the struggles faced by black people in the diaspora through the lens of the Duboisian narrative of double-consciousness. It is argued here that white people, through their alleged guilt, cause more damage than good. For context, Abdulrazak Gurnah’s Admiring Silence is analysed as it eloquently captures white guilt and its consequences. Findings reveal that the form of social justice practised by white people, stemming from white guilt, gives white people a sense of superiority and causes harm to the psyche, and ultimately lives, of black people.